Drug Utilization Study on Oral Contraceptives provided from Social Security, Buenos Aires-Argentina: Risk and cost analysis according to the type of combination used - Marin, Lupe (2020)
Oral contraceptive pill is the most prescribed option to avoid birth-rate around the world. It is a combination of estrogens/progestin.Unfortunately, new combinations raise the risk of thrombosis. To determine the prescription profile and the incidence of thro mbotic eventsassociated to oral contraceptive use, we developed the present study.Method: It is a drug utilization study among beneficiaries of Buenos Aires Social Security Organization. Variables studied were age, sex,combination consumed, doses, co-morbidities, thrombotic events.Results: 69,653 women were enrolled in the study. 66,043 of them (94.84%) used new progestogen generation combination (desogestrel,gestodene, drospirenone,) while 3610 (5.18%) used either levonorgestrel or norgestrel as progestin. The number of thrombotic events (eitherdepth vein thrombosis of lower limbs, thromboembolism or arterial thrombosis) was 77 (75 with new progestin and 2 using 1st/2nd generationoptions). Adjusting these values to 100,000 users; the occurrence of thrombotic events were doubled with new generation progestins whencompared to older options. The price of the new generation combinations were 10.2 times more expensive that the safer ones.Conclusion: Among the beneficiaries of Buenos Aires State Social Security, the users of oral contraceptives with new generation progestindenote a greater risk of thrombotic events when compared with users of levonorgestrel or norgestrel. Public reproductive health policies thatprovide contraceptives to the population are crucial in guaranteeing rights such as avoiding unwanted pregnancies and reproductive planning.However, the combinations provided should not expose population to additional and unnecessary risks.